explain this and solve
Attachments:
![](https://hi-static.z-dn.net/files/d97/f00982ae06bdd792eab48125d374462b.jpg)
Answers
Answered by
8
Refer to the attachment!
•••••••••••••••••••••••••••••••••••••••
Hope you get helped!!!!
#BeBrainly
~@yash197911
Attachments:
![](https://hi-static.z-dn.net/files/d71/25a7e00488c071ac64bab8d0bc73c64e.jpg)
Answered by
2
Step-by-step explanation:
x+2/6 - (11-x/3 - 1/4) = 3x - 14 / 12
opening bracket
x + 2/6 -11+x/3 + 1/4 = 3x-14/12
LET ALL THE TERMS HAVE A DENOMINWTOR OF 12
=> 2x+4/12 - 44+4x/12 + 3/12 = 3x-14/12
2x+4/12 + 3/12 = 3x-14+44+4x/12
2x + 4/12 + 3/12 = 7x+30/12
2x+7/12 = 7x+30/12
- 7/12 on all sides
2x = 7x - 23/12
23/12 = 7x - 2x
23/12 = 5x
= 23/60 = x
Similar questions